Cruise observation of the marine atmosphere and ship emissions in South China Sea: Aerosol composition, sources, and the aging process. (1st January 2023) - Sun, Qibin; Liang, Baoling; Cai, Mingfu; Zhang, Yongyun; Ou, Hengjia; Ni, Xue; Sun, Xi; Han, Bo; Deng, Xuejiao; Zhou, Shengzhen; Zhao, Jun
Abstract: Marine atmospheric aerosols impact the global climate and biogeochemical cycles. However, how the composition, sources, and aging of these aerosols affect the above processes has not been thoroughly studied. Here, we conducted ship-based measurements in the northern South China Sea to investigate the chemical composition and aging of aerosols from various sources during the summer of 2019. Separate measurements were conducted at the bow (marine environment) and stern (cooking, smoking, and engine exhaust) of the ship. Source apportionment of organic aerosols (OAs) was conducted using positive matrix factorization (PMF) and trajectory models. The results showed that ship exhaust and coastal submicron particles were composed of comparable sulfate and organic fractions (both approximately 43%), distinct from the sulfate-dominated particles in the marine atmosphere (52–77%). PMF using the multilinear engine-2 solver identified five factors for the stern sampling period: hydrocarbon-like OA (HOA-I, 9%), slightly oxidized HOA (HOA-II, 25%), cooking OA (COA, 13%), cigarette smoke OA (CSOA, 4%), and low-volatility oxygenated OA (LV-OOA, 49%). The primary OAs (HOA-I/II + COA + CSOA), derived mostly from direct ship-related emissions, contributed to approximately half of the OAs, whereas the contribution from the highly aged marine atmosphere was only 20%. Notably, certain living-related emissions (i.e., COA and CSOA), which were often neglected in previous studies, might represent a considerable contribution to OA emissions from the ship. Four factors were identified for the bow sampling periods: HOA (13%), biomass burning OA (BBOA, 9%), semi-volatile OOA (7%), and LV-OOA (71%). The BBOAs from the Indo-China and Malay peninsulas were aged, converted to secondary organic aerosols (SOAs) during transport, and influenced by the combined photo-oxidation and liquid-phase reactions, indicating a substantial impact of BB on SOA formation. Our study highlights the influence of ship and inland emissions and their aging during transport on marine atmospheric aerosols. Graphical abstract: Image 1 Highlights: Primary organic aerosol (OA) from ship emissions contributes to about half of OA. Marine atmospheric aerosols are highly aged with about 80% secondary OA of total OA. Biomass burning OA was aged by combined photo-oxidation and liquid-phase reactions. The cooking and smoking OAs constitute a considerable fraction of ship emissions.